Edge plane pyrolytic graphite electrodes for stripping voltammetry: A comparison with other carbon based electrodes - Wantz, F; Banks, C; Compton, R (2005)
The first examples of using edge plane pyrolytic graphite electrodes for anodic and cathodic stripping voltammetry (ASV and CSV) are presented, notably the ASV of silver and the CSV of manganese. In the former example, detection limits for silver (based on 3σ) of 8.1 nM and 0.185 nM for 120 s and 300 s accumulation time, respectively, were achievable using the edge plane electrode, which were superior to those observed on glassy carbon, basal plane pyrolytic graphite and boron-doped diamond electrodes. In the second example, a detection limit for manganese of 0.3 μM was possible which was comparable with that achievable with a boron-doped diamond electrode but with an increased sensitivity. Comparison of the edge plane pyrolytic graphite electrode with boron-doped diamond electrodes reveals that the edge plane electrode has comparable detection limits and sensitivities whilst exhibiting a lower signal-to-noise ratio and large potential window for use in trace analysis suggesting boron-doped diamond can be conveniently replaced by edge plane pyrolytic graphite as an electrode material in many applications. © 2005 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.